2015
DOI: 10.5604/12321966.1152088
|View full text |Cite
|
Sign up to set email alerts
|

Activity of MMP-2, MMP-8 and MMP-9 in serum as a marker of progression of alcoholic liver disease in people from Lublin Region, eastern Poland

Abstract: In alcoholic liver cirrhosis, normal liver cells are replaced by scar tissue (fibrosis). Liver fibrosis is a dynamic process in which activated hepatic stellate cells are involved in the synthesis of matrix proteins and the regulation of matrix degeneration. The aim of the presented study was to assess the usefulness of MMP-2, MMP-8 and MMP-9 as diagnostic markers of alcoholic liver disease. Sixty patients with alcoholic liver cirrhosis were randomly enrolled during hospitalization in departments of hospitals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 0 publications
3
19
0
1
Order By: Relevance
“…In addition, MMP-8 was considered to promote collagen breakdown 42. The data confirmed that, along with more HSCs were activated in CCl 4 -treated mice, the level of MMP-8 in these mice was increased to degrade the collagen.…”
Section: Discussionsupporting
confidence: 54%
“…In addition, MMP-8 was considered to promote collagen breakdown 42. The data confirmed that, along with more HSCs were activated in CCl 4 -treated mice, the level of MMP-8 in these mice was increased to degrade the collagen.…”
Section: Discussionsupporting
confidence: 54%
“…Our finding that MMP-2 levels were elevated also in non-HCV cirrhotics is in accordance with recent observation by Prystupal et al, (2015) (32) who found that MMP-2 activity in sera of patients with different stages of alcoholic liver cirrhosis was significantly increased compared to the control group. They showed also that among other MMPs, MMP-2 has been found to be the most sensitive as its activity was increased in all stages of liver cirrhosis.…”
Section: Discussionsupporting
confidence: 82%
“…Si bien Sillanaukee y colegas (2002) (18) mostraron elevaciones de proteína MMP-9 en alcohólicos finlandeses probablemente debido a la condición inflamatoria general crónica que sufren los alcohólicos (11) , los aumentos eran menores y no habían reportado cambios en MMP-2. Analizando pacientes del este de Polonia, Prystupa y colegas (2015) (29) encontraron niveles aumentados de MMP-2, MMP-8 y MMP-9 solo en las etapas cirróticas en alcohólicos cirróticos hepáticos, pero no antes. En cambio, nuestros resultados no están de acuerdo con los datos obtenidos por Madro y cols.…”
Section: Discussionunclassified